KADAR CALPROTECTIN CAIRAN SULKUS GINGIVA PADA KEDALAMAN POKET PERIODONTAL YANG BERBEDA PENDERITA AGGRESSIVE PERIODONTITIS - Sari, Desi Sandra (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Aggressive Periodontitis is a form of periodontitis which is characterized with the presence of deep pocket, rapid loss of connective tissue attachment and alveolar bone. The rapid damage is caused by the dysfunction chemotaxis and phagocytosis from neutrophil.Calprotectin is a major cytosolic protein of neutrophils, monocytes and epithelial cells. The calprotectin level in gingival crevicular fluid is useful marker for evaluation the progression of inflammation in periodontitis disease. In this study, we investigated calprotectin level at different periodontal pocket depth from patient with aggressive periodontitis. This research involved twelve subjects who had been diagnosed as suffered from aggressive periodontitis. Their gingival crevicular fluid was taken from different periodontal pocket depths (slight â¤3mm, moderate 4-6mm, severe â¥ 7 mm), using sterile papperpoints. Level of calprotectin in gingival crevicular fluid were analysed by enzyme-linked immunosorbent assay (ELISA) procedures. The result showed that gingival crevicular fluids calprotectin level increased approximately in proportion to probing depth slight, moderate, and severe (p< 0,05), and showed a significant positive correlation with probing depth (R=0,776, p< 0,05). This research concluded that the calprotectin level in gingival crevicular fluid is positively related to clinical indicators (probing depth) and reflect the degree of gingival inflamation in patient with aggressive periodontitis